Study Of Root Development In Vegetative Cloned Sal Plants Vis-A-Vis Plants Raised from Seeds - Singh, Lal Ratnakar (Indian Forester, 2014)
Different soil types and their properties are important factors in determining rooting habit of a tree. Artificially regenerated sal plants, especially raised by cuttings, rooted in mist chambers, develop their root system differently. In the artificially raised sal plants in poly bags from seeds and from pre sprouted root-shoots, the initial root system starts as a single tap root. On the contrary, when cuttings are rooted in mist chamber, the root system is entirely different and it comes up as thin bunch of fine rootlets which, later on, transforms into multiple tap root like structures. Such roots have more surface area at interface with soil and, thus, enhances absorption of water and nutrients. This study reveals the cause of the accelerated initial growth of sal plants raised from cuttings rooted in mist chamber by studying and comparing the root architecture of these plants in initial stages vis-a-vis the plants raised from seeds and pre-sprouted root-shoots.